Freshwater and brackish water fishes of Sakhalin Island (Russia) in inland and coastal waters: an annotated checklist with taxonomic comments - Dyldin, Yury V.; Fricke, Ronald; Hanel, Lubomir; Vorobiev, Danil S.; Interesova, Elena A.; Romanov, Vladimir I.; Orlov, Alexei M. (Zootaxa, 2021)
Based on a critical analysis of scientific publications for the last 200 years and on the collected specimens, a complete annotated list of both typical freshwater ichthyofauna of Sakhalin Island, with the inclusion of marine species that can be found in brackish coastal waters, is reported for the first time. The annotated list includes 226 species classified in three classes, 26 orders, 68 families, 29 subfamilies, and 148 genera. For 160 species, information is provided on collection samples deposited in various museums around the world, 36 of which are type specimens. For each species, conservation status (according to IUCN Red List of Threatened Species and the Red Book of the Sakhalin region), zoogeographic characteristics (distribution within Sakhalin Island and globally), abundance and commercial value are given. For a number of species, more detailed information on synonymy and nomenclature is provided. The study area is located in the western North Pacific and includes the entire coast of Sakhalin Island in the Sea of Okhotsk and the northern Sea of Japan, as well as the adjacent Sea of Okhotsk coast of northern Hokkaido, Japan.